Eficiência reprodutiva e comportamento parental de camundongos isogênicos e heterogênicos produzidos em ambiente modificado - Moreira, Virgínia Barreto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the preference and effect of nesting materials provision on performance of inbred mice of the BALB/c strain and of heterogenic Swiss in intensive monogamous mating system. Firstly, a study was conducted to evaluate the preference of mice for the material offered for nesting. A system composed of four cages was used, with free access to water and food, connected by PVC tubing, which allowed animal displacement among all cages. Four types of materials were available for construction of the nest: cotton, gauze, cardboard rolls, and disposable polypropylene cap. Each of the four materials was offered simultaneously in one of four cages that formed the system. Ten identical system were used and each one housed a BALB/c couple, from 28 days of age up to the third reproductive cycle. The most commonly found materials in nest making were cap, roll, cotton and gauze (P <0.0083). Based on these results, two types of materials were selected to be offered to the animals in experiment 2. Although the roll was the second most used material, we chose cotton due to unfeasibility supplying of the item throughout the duration of the second experiment. The second experiment evaluated the reproductive efficiency in five reproductive cycles from birth to weaning. Sixty BALB / c full siblings pairs (inbred) and 60 pairs formed by random mating of Swiss strain (outbred), bred and maintained in a standardized environment were used. They were distributed in a completely randomized design in a 2x2 factorial arrangement (two strains in housing with or without nesting material). As a way of cage enrichment, polypropylene disposable cap cut into 8 pieces of approximately 1 cm each and one piece of cotton about 3 g were used after being previously packaged and autoclaved . The following characteristics were evaluated: age at first parturition, litter intervals, pre-weaning mortality and ...

O objetivo deste estudo foi avaliar a preferência e efeito do fornecimento de materiais de nidificação sobre o desempenho reprodutivo de camundongos isogênicos da linhagem BALB/c e da linhagem heterogênica Swiss em sistema de acasalamento intensivo monogâmico. Primeiro foi realizado um estudo para avaliar a preferência dos camundongos pelo material oferecido para nidificação. Utilizou-se um sistema composto de quatro gaiolas, com livre acesso a água e ração, interligados por tubos de PVC que permitiam que os animais se locomovessem entre todas as gaiolas. Quatro tipos de materiais foram oferecidos para a construção do ninho: algodão, gaze, rolinho de papelão, e touca de polipropileno descartável. Cada um dos quatro materiais foi oferecido simultaneamente em uma das quatro gaiolas que compunham o sistema. Foram usados 10 sistemas iguais e cada um abrigou um casal da linhagem BALB/c, desde os 28 dias de idade até o terceiro ciclo reprodutivo. Os mais encontrados na confecção do ninho, em ordem decrescente, foram a touca, rolinho, algodão e gaze (P< 0,0083). Com base nestes resultados foram selecionados dois tipos de materiais para fornecimento aos animais no experimento 2. Embora o rolinho tenha sido o segundo material mais utilizado optou-se pelo algodão devido a inviabilidade de fornecimento do item durante todo o período de duração do experimento 2. O segundo experimento avaliou a eficiência reprodutiva em cinco ciclos reprodutivos do nascimento até o desmame. Usou-se 60 casais de irmãos completos da linhagem BALB/c (isogênica) e 60 casais formados por acasalamentos aleatórios da linhagem Swiss (heterogênica) de padrão sanitário controlado, criados e mantidos em ambiente padronizado. Eles foram distribuídos, num delineamento inteiramente casualizado, em arranjo fatorial 2x2 (duas linhagens em alojamento com ou sem material para nidificação). Como forma de ...
Keywords: Camundongo como animal de laboratorio - Reprodução; Animais - Proteção; Animais - Criação; Mice as laboratory animals